The Influence of Live Streaming Shopping, Twin Date Promotion, and E-WOM on Gen Z Shopee Users' Impulse Buying in Surabaya - Salwanisa, Estetia Adistsany; Fitriyah, Zumrotul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study explores how live streaming shopping, twin event promotions, and E-WOM impact impulse buying behavior among Gen Z users of the Shopee e-commerce platform. It is intended to serve as a scholarly reference for future research. The study employed a quantitative descriptive approach, utilizing Partial Least Squares (PLS) for data analysis. The results suggest that while live streaming shopping and E-WOM do not affect impulse buying behavior among Gen Z users of Shopee in Surabaya, twin event promotions contribute to their impulse buying behavior.